Changing housework, changing health? A longitudinal analysis of how changes in housework are associated with functional somatic symptoms. Issue 1 (1st January 2016) - Landstedt, Evelina; Harryson, Lisa; Hammarström, Anne
Abstract : Aim: The aim of this study was to analyse how changes in housework over the course of adulthood are related to somatic health in Swedish men and women. Methods: Data were drawn from 2 waves of the Northern Swedish Cohort Study, response rate 94.3%, N=1, 001. A subsample of cohabiting individuals was selected (n=328 women, 300 men). Outcome variable was functional somatic symptoms (FSS) at age 42. Associations were assessed in multivariate general linear models with adjustment for confounders and somatic health at age 30. Results: Housework is primarily performed by women, and women's responsibility for and performance of housework increased from ages 30 to 42. These changes were associated with elevated levels of FSS at age 42 in women. Men reported considerably lower responsibility for and performed less housework compared with women, the load of housework for men does not change substantially from ages 30 to 42 and no associations with FSS were identified. Conclusions: The gendered division of housework means that women are particularly exposed to a heavy workload. Women's responsibility for and performance of housework increase between ages 30 and 42 and this threatens to be embodied in the form FSS. We conclude that housework should be considered an important source of stress in addition to that from waged work and that a deeper understanding of the links between housework and health requires a gender theoretical analysis.